Microstructural evolution of cross-linked polytetrafluoroethylene under gamma irradiation using ultra-small angle X-ray scattering. (September 2022) - Sha, Feixiang; Cheng, Guojun; Li, Xiuhong; Tian, Feng; Tang, Zhongfeng
Highlights: Microstructural evolution of XPTFE were firstly studied using in-situ USAXS. The size and spacing of scatterers are more unequal in XPTFE. Lamellae crystals in XPTFE are elongated and thinned along the tension direction. Broken crystals and voids in irradiated XPTFE are oriented with stretching. Abstract: Cross-linked polytetrafluoroethylene (XPTFE) with excellent wear and radiation resistant is expected to be applied in strong radiation fields. In this study, synchrotron ultra-small angle X-ray scattering (USAXS) techniques combined with in-situ uniaxial stretching were firstly used to study the mechanical property degradation mechanism of XPTFE in terms of micro-structural evolution in real time. As the increase of cross-linking degree, the size and spacing of the scatterers for XPTFE were more unequal. When XPTFE was uniaxially stretched at room temperature, its molecular chains were tilted, and lamellae crystals were elongated and thinned along the stretching direction. When XPTFE was irradiated by γ-rays under air, with increasing absorbed doses, the long period decreased first and then increased, while the gyration radius was reversed. After high-dose irradiation, the mechanical properties of XPTFE were lost, making their stretching processes were dominated by the orientation of some small broken crystals along the stretching direction and accompanied by the formation of voids. But for XPTFE under constant stress uniaxial stretching at variable temperature, its chain segments and molecular chains cannot be oriented even at elevated temperatures, maintaining a degree of thermal stability.